Has noninvasive prenatal testing impacted termination of pregnancy and live birth rates of infants with Down syndrome?. (29th December 2017) - Hill, Melissa; Barrett, Angela; Choolani, Mahesh; Lewis, Celine; Fisher, Jane; Chitty, Lyn S.
Abstract: Background: Implementation of noninvasive prenatal testing (NIPT) as a highly accurate aneuploidy screening test has raised questions around whether the high uptake may result in more terminations of pregnancies and fewer births of children with Down syndrome (DS). Aim: The aim of the study was to investigate the impact of NIPT on termination and live birth rates for DS. Methods: Literature reporting pregnancy outcomes following NIPT was reviewed . Termination rates were calculated for women with a high‐risk NIPT result for DS. Two audits of pregnancy outcomes where NIPT indicated DS were conducted in the United Kingdom and Singapore. Results: Fourteen studies from the United States, Asia, Europe, and the United Kingdom were included in the review. Live births of children with DS were reported in 8 studies. Termination rates following NIPT were unchanged or decreased when compared to termination rates prior to the introduction of NIPT. Audits found 15 of 43 women in the United Kingdom and 2 of 6 in Singapore continued pregnancies following a high‐risk NIPT result. Conclusions: Termination rates following the detection of DS by NIPT are unchanged or decreased compared to historical termination rates. Impact on live birth rates may be minimal in settings where termination rates fall. Population‐based studies are required to determine the true impact. Abstract : WHAT IS ALREADY KNOWN ABOUT THIS TOPIC? Noninvasive prenatal testing (NIPT) has been shown to be a highly accurate prenatal screening test for DS and is being implemented widely throughout the world. Introduction of NIPT has increased the prenatal detection of DS with a significantly reduced invasive testing rate, but the impact on rates of termination of pregnancy and the number of children born with DS is not yet known. WHAT DOES THIS STUDY ADD? Introduction of NIPT has a variable effect on termination rates for DS, but rates have remained unchanged or decreased when compared to termination rates reported prior to the introduction of NIPT, with many parents using NIPT for information and continuing pregnancies when results show a high risk of DS. Practical and emotional support structures are needed for these families. Where termination rates fall NIPT may have a minimal impact on live birth rates for DS. Monitoring at population levels is required for a more accurate assessment of live birth rates.